Emergent coordination of heading in soccer: Of two players and a single ball - Smith, D.; Zaal, F. T. J. M.; Memmert, D. (Research Quarterly for Exercise and Sport, 2023)
Purpose: In many sports situations, two or more players need to coordinate their actions to make sure that one of them intercepts a ball or opponent. We considered how two soccer players head back a thrown ball. Two accounts for the joint decision making by both players were considered. These two accounts not only differ in their theoretical basis but also have vastly different implications for training practice. In a first account, players know their areas of responsibility for interception, and combine this with their prediction of the ball's landing location. In a second account, the coordination emerges from the unfolding dynamics of the system of informationally connected players and ball. According to this second account, especially for balls aimed in between the two players, both of the players may start moving and one player sees that the ball will be interceptable for the other player, and subsequently yields the interception.